A simple lysimeter for soil water sampling in south Florida - Kati W. Migliaccio; Yuncong Li; Harry Trafford; Edward Evans (EDIS, 2006)
This document is ABE 361, from the Department of Agricultural and Biological Engineering, UF/IFAS Extension. First published March 2006.